Determinação da capacidade antioxidante dos extratos da casca de Rhizophora mangle: uma abordagem contextualizada no ensino de química analítica instrumental - Damm, Bruna Marine (2023)
Rhizophora mangle, a typical mangrove plant, plays a relevant socio-environmental role for communities living around the ecosystem. In Espírito Santo, the bark of the plant is used in the making of the capixaba clay pan. In other parts of the world, people report its use for medicinal purposes, due to its chemical composition, rich in antioxidants. Thus, this context was used as a reference for the application of the chemical knowledge covered in the discipline of analytical chemistry IV, of the bachelor's degree in chemistry, at the University Federal of Espírito Santo (Ufes). Initially, the researcher verified the antioxidant potential of the hydroethanolic extract of the plant bark. The extract showed a high content of total phenols of 91.4 ± 1.2 mg gallic acid equivalent (mg GAE)/g of bark) and antioxidant capacity by FRAP (ferric reducing antioxidant power) and CRAC (ceric reducing antioxidant capacity) assays, with trolox equivalent (TE) values of 15.2 ± 2.5 and 12.4 ± 0.7, respectively. Subsequently, a didactic strategy was applied in teaching chemistry, in the light of problem-based learning (PBL). The target audience was 27 students of analytical chemistry IV (theoretical and experimental). The sequence of actions was divided into six meetings, totaling 18 hours, in hybrid mode, with face-to-face and remote moments. The students got to know closely the plant in the mangrove and its use as raw material in the manufacture of capixaba clay pans. In a chemistry laboratory, they used the analytical techniques discussed in the course for the spectrophotometric (FRAP assay) and electrochemical (CRAC assay) determination of the total antioxidant capacity of extracts from the bark of Rhizophora mangle. The extracts showed significant antioxidant capacity: hydroethanolic extract (prepared by the researcher) > hydroethanolic extract (prepared by the students) > aqueous extract (prepared by the students) > aqueous extract (prepared by the manufacturers the clay pan) > trolox. The students acted to disseminate the results, based on the following purpose: how can chemistry bring scientific information and contributions to potters and society? Information was collected through a logbook, questionnaires, practical class reports, sheets, and PBL products. The evaluation by rubrics and the PBL methodology employed was based on the five-point Likert scale. As for the contributions of the teaching strategy in the student's formation, it is inferred that the activities worked in a contextualized way and focused on solving problems, mobilized skills such: as collaboration, critical view of the subject, communication, creativity, and ability to argue based on the chemical knowledge learned in the course. From the content analysis (CA) combined with the Iramuteq® software, it was possible to discuss and show graphically (descending hierarchical classification-DHC, factorial analysis of correspondence-FAC and word cloud) how the Rhizophora mangle context was related to chemical knowledge and chemistry teaching. Thus, the set of educational, theoretical, and experimental studies with the plant enabled the articulation of multiple knowledge/knowledge (pedagogical, scientific, popular, and cultural).